Experimental and numerical study of the thermomechanical behaviour of wood-based panels exposed to fire. (30th January 2018) - Cueff, Guillaume; Mindeguia, Jean-Christophe; Dréan, Virginie; Breysse, Denys; Auguin, Gildas
Highlights: Experimental and numerical study of the fire behaviour of wood panels is proposed. A thermomechanical model is developed, including thermal reactions in the material. Main Thermomechanical properties of the wood panels are measured. Simulations show good results and could help the fire development of the products. Abstract: A research programme has been set up whose main objective is to build a thermo-mechanical model for simulating fire resistance tests on door sets composed of wood-based materials. Based on simulated temperature field and on estimations of the global bending of the fire door, the model should allow parametrical studies to be carried out in order to determine the behaviour of the product in a real fire resistance test. This should lead to a reduction in the number of high-cost real tests. A numerical model for fire degradation of wood-based products was developed first. Then, the results of thermal and mechanical characterisations of wood-based products (particle boards) are presented. Finally, simulations of thermal transfers and the thermomechanical behaviour of a small-scale door were carried out. The numerical results are compared to experimental data and show good agreement on thermal transfers and temperatures on the unexposed side of products. The simulated deformation of the panel is similar to the observation during the test. Nevertheless, the evolution of the displacement during the fire is not yet well transcribed. Possibilities for improving the mechanical model are then indicated.